2015
DOI: 10.1016/j.egypro.2015.03.286
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Si Surface Structure by Ag/Al Contact Spots – An Explanatory Model

Abstract: In the past years, the contact formation of Ag screen-printing pastes to n + emitters has been profoundly investigated and at least in parts explained. However, p + emitters cannot be contacted well with standard Ag pastes. It has been shown that adding Al to Ag screen printing pastes leads to lower contact resistances. Therefore different mechanisms must play a role in the contact formation process. The role of Al and the exact mechanism of contact formation of these Al containing Ag screen-printing pastes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In this model, contacts grow in localized areas through openings of the SiNx:H coating, and SiNx:H acts as a mould during the growth of the Ag/Al contacts spots ( Fig. 1) [12][13][14][15]. Furthermore, it was shown that increasing the Al content limits the densification of the screenprinted metal and leads to modified glass distribution in the interface structure [16,17].…”
Section: Fundamental Understanding Of Screen Printed Contactsmentioning
confidence: 98%
“…In this model, contacts grow in localized areas through openings of the SiNx:H coating, and SiNx:H acts as a mould during the growth of the Ag/Al contacts spots ( Fig. 1) [12][13][14][15]. Furthermore, it was shown that increasing the Al content limits the densification of the screenprinted metal and leads to modified glass distribution in the interface structure [16,17].…”
Section: Fundamental Understanding Of Screen Printed Contactsmentioning
confidence: 98%
“…The wafers were treated in different ways to realize different surface structures: Wafers were either etched in NaOH to realize plane (100)-oriented surfaces or alkaline textured to obtain a pyramidal surface texture with (111)-oriented pyramid planes or plasma textured [16]. After cleaning, a 50-Ω/ emitter was diffused in a BBr 3 -based open tube furnace process.…”
Section: Sample Preparation and Experimental Detailsmentioning
confidence: 99%
“…However, up to now, most studies dealing with the microstructure of screen-printed Ag/Al contacts were based on scanning electron microscopy (SEM) analysis and, therefore, lack of information about the crystallographic structure and orientation of the Ag/Al contact spots [11], [15], [16]. In addition, the spatial resolution of SEM energy-dispersive X-ray (EDX) spectroscopy is limited to >1 μm as a result of the large activation volume of the electrons in a bulk sample.…”
Section: Introductionmentioning
confidence: 99%